ANALISIS SISTEM INFORMASI KUALITAS PRODUKSI SULAMAN MAYANG DENGAN MENGGUNAKAN METODE MC CALL - Firna Yenila; Eva Rianti (STMIK Royal, 2020)
Abstract: Sulaman Mayang's Industry has implemented a desktop-based system in data processing, a one-way system involving only one actor/user of the system. So that in use there are some new problems that have arisen that affect the performance of services to customers. This study aims to analyze and test the quality of the Mayan embroidery information system using the McCall method. Analysis is carried out on several aspects of the product operation including the quality factors of correctness (truth), reliability (reliability), efficiency (efficiency), integrity (integrity) and usability (usability). Data was collected through questionnaires from 38 respondents involving workers/employees and customers. The results showed that overall the quality of the Sulaman Mayang information system was at the level of 76% (the quality of the information system was good according to the scale interpretation of the percentage of quality factors). Thus the quality of Mayang embroidery information systems needs to be improved in accordance with recommendations which are improvements to the quality of Mayan embroidery information systems. Keywords: McCall Method; Sulaman Mayang; the quality of information system. Abstrak: Industri Sulaman mayang sejauh ini menerapkan sistem berbasiskan dekstop dalam pengolahan data, sistem yang digunakan satu arah hanya melibatkan satu aktor/pengguna sistem saja. Sehingga dalam penggunaan ada beberapa persoalan baru yang bermunculan yang mempengaruhi kinerja layanan terhadap pelanggan. Penelitian ini bertujuan untuk menganalisa dan menguji kualitas sitem informasi sulaman mayang dengan meggunakan metode McCall. Analisa dilakukan terhadap beberapa aspek dalam product operation diantaranya faktor kualitas correctness (kebenaran), reliability (keandalan), effisiensy (efisien), integrity (integritas) dan usability (kegunaan). Data dikumpulkan melalui kuosioner dari 38 responden yang melibatkan pekerja/karyawan dan pelanggan. Hasil penelitian menunjukkan bahwa secara keseluruhan kualitas sistem informasi sulaman mayang berada pada level 76% (kualitas sistem informasi tersebut baik menurut skala penafsiran persentase faktor kualitas). Dengan demikian kualitas sistem informasi sulaman mayang perlu ditingkatkan sesuai dengan rekomendasi yang merupakan perbaikan kualitas sistem informasi sulaman mayang. Kata kunci: kualitas sistem informasi; metode McCall; Sulaman Mayang